A Self‐Healing Crease‐Free Supramolecular All‐Polymer Supercapacitor. Issue 12 (1st May 2021) - Mo, Funian; Li, Qing; Liang, Guojin; Zhao, Yuwei; Wang, Donghong; Huang, Yan; Wei, Jun; Zhi, Chunyi
Abstract: While traditional three‐layer structure supercapacitors are under mechanical manipulations, the high‐stress region concentrates, inevitably causing persistent structural problems including interlayer slippage, crease formation, and delamination of the electrode–electrolyte interface. Toward this, an all‐polymeric, all‐elastic and non‐laminated supercapacitor with high mechanical reliability and excellent electrochemical performance is developed. Specifically, a polypyrrole electrode layer is in situ integrated into a silk fibroin‐based elastic supramolecular hydrogel film with extensive hydrogen and covalent bonds, where a non‐laminate device is realized with structural elasticity at the device level. The non‐laminate configuration can avoid slippage and delamination, while the elasticity can preclude crease formation. Furthermore, under more severe mechanical damage, the supercapacitors can restore the electrochemical performance through non‐autonomous self‐healing capabilities, where the supramolecular design of host–guest interactions in the hydrogel matrix results in a superior self‐healing efficiency approaching ≈95.8% even after 30 cutting/healing cycles. The all‐elastic supercapacitor delivers an areal capacitance of 0.37 F cm −2 and a volumetric energy density of 0.082 mW h cm −3, which can well‐maintain the specific capacitance even at −20 °C with over 85.2% retention after five cut/healing cycles. Abstract : An integrated all polymer‐based supercapacitor with superior reliability and durability is developed, which exhibits a self‐healing efficiency approaching 100% via supramolecular chemistry of host–guest interactions between β ‐cyclodextrin and amino acid side chains of silk fibroin.